Efficiency optimization of a two-port microwave oven: a robust automated procedure. Issue 4 (6th July 2015) - Bressan, Fernando; Dughiero, Fabrizio; Bullo, Marco; Di Barba, Paolo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In the paper, a single-objective optimization problem characterized by high-frequency field analysis is investigated: the optimal design of a two-port microwave (MW) oven, taking into account the possibility of two independently controlled sources, with the aim of improving the efficiency is considered as the case study. The paper aims to discuss these issues. Design/methodology/approach – A high-frequency field analysis has been coupled to a robust evolutionary-computing algorithm in order to create an appropriate procedure for the optimal design of a MW oven based on a cascade optimization: in the first step the optimized geometry has been identified, while in the second step the optimized electrical supply values have been synthesized. In particular, the direct problem has been faced by means of a 3D-FEM approach in order to obtain realistic results; the inverse problem has been faced by means of a derivative-free robust algorithm based on evolutionary strategy in order to get a fast convergence of the solution. Findings – A new design procedure for high efficiency MW ovens for household application by means of the proposed numerical approach. Practical implications – These results allow industrial designers to improve this kind of devices. Originality/value – The original contribution of the paper is the systematic approach to the optimal design of a MW oven with multiple feeding, based on the link between an algorithm of evolutionary strategy optimization algorithm and a finite-element solver.